ELEMENTARY WEIGHTINGS ON FUNCTIONS AND TEACHING OF LITERATURE - Cleiton Cardoso Batista, Francisco (Revista Gênero e Interdisciplinaridade, 2023)
This work discusses the functions and the teaching of literature. This was done with the aim of drawing attention to the importance of teachers also reflecting on the multiple ways of approaching the literary text in the classroom, since the functions of literature are also multiple. These approaches can be philosophical, sociological, historical; ethical and moral, but there should be no detriment to the linguistic, grammatical and philological approaches, since meaning and form are inseparable in a text. As theoretical support, we base ourselves – more directly – on Coutinho (2015), Proença Filho (2012) and Moisés (2013). There are several questions about the type of approach that should (should) be in the classroom when the subject is literature. We intend to discuss the many gains present in each type of approach.